2022
DOI: 10.1177/07067437221136468
|View full text |Cite
|
Sign up to set email alerts
|

Methadone Maintenance Treatment Discontinuation Among Young People who use Opioids in Vancouver, Canada

Abstract: Objective Retaining adolescents and young adults (AYA) in medications for opioid use disorder (MOUD), like methadone maintenance treatment (MMT), is critical to reducing toxic drug fatalities. This analysis sought to identify factors associated with MMT discontinuation among AYA. Method Data were derived from the At-Risk Youth Study, a prospective cohort study of street-involved AYA in Vancouver, Canada, between December 2005 and June 2018. Multivariable extended Cox regression identified factors associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Pilarinos et al [ 36 ] examined factors associated with time to methadone discontinuation among a sample of youth (aged 14–26) engaged in methadone in Vancouver, Canada. Discontinuation was defined as individuals who indicated they had received MMT in the last 6 months but were not currently on MMT during data collection.…”
Section: Resultsmentioning
confidence: 99%
“…Pilarinos et al [ 36 ] examined factors associated with time to methadone discontinuation among a sample of youth (aged 14–26) engaged in methadone in Vancouver, Canada. Discontinuation was defined as individuals who indicated they had received MMT in the last 6 months but were not currently on MMT during data collection.…”
Section: Resultsmentioning
confidence: 99%
“…Participants’ experiences with drug treatment offer insight into the low retention rates for medications to treat opioid use disorder observed in numerous studies. Many studies have examined individual level factors that are associated with poor retention in MOUD and other drug treatment programs including polysubstance use, more severe opioid use disorder and homelessness [ 18 , 29 , 31 , 32 , 52 ]. The implication from these studies seems to be that polysubstance users are unable to adhere to MOUD and that they require additional services, including treatment options, such as contingency management, to address their other substance use and psychosocial needs.…”
Section: Discussionmentioning
confidence: 99%
“…The implication from these studies seems to be that polysubstance users are unable to adhere to MOUD and that they require additional services, including treatment options, such as contingency management, to address their other substance use and psychosocial needs. However, many of these barriers may very well be at the organizational level with polydrug users more likely to fail urine drug screens and be discontinued in treatment [ 31 ]. Many times, these additional drugs did not decrease the safety of MOUD, and it was not clear that programs were offering services to address other substance use problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methadone is used to prevent opiate withdrawal. Methadone is a synthetic opioid analgesic, similar to morphine, but with a longer duration of action and less abuse potential (15). Iyengar et al showed that, the relationship between zinc and the immune system, and reported that drug addicts are susceptible to various infections such as hepatitis and acquired immunode ciency syndrome, as well as concern about the excessive urinary loss of zinc in this group (16).…”
Section: Discussionmentioning
confidence: 99%